Atraumatic Multilobulated Lateral Meniscal Cysts in Younger Patients: A case report - Wiboonthanasarn, Nuttara; Interasampan, Piyapong; Roongnim, Bundit (Journal of Southeast Asian Orthopaedics, 2021)
The incidence of meniscal cysts, a relatively rare condition in orthopedics, ranges from 1-8% of cyst cases(1). A typical meniscal cyst is from 0.3 to 9 mm. in diameter(2). We report on a 32-year-old male patient who presented with swelling and a large, slow growing mass at the anterolateral side of the right knee. Arthroscopic examination was conducted, and debridement was performed with good results and a satisfactory outcome. No complications were detected at 12 months post-surgery.